Regioisomers of Organic Semiconducting Dumbbell‐Shaped Molecules: Synthesis and Structure‐Properties Relationship. Issue 22 (8th June 2021) - Mahmoudi, Chaima; Bulut, Ibrahim; Jing, Jiang; Fall, Sadiara; Heinrich, Benoît; Méry, Stéphane; Heiser, Thomas; Lévêque, Patrick; Steveler, Emilie; Majdoub, Mustapha; Leclerc, Nicolas
Abstract: Two new dumbbell‐shaped molecules based on two solubilizing and structuring triazatruxene (TAT) units linked by a central chromophore were synthesized and studied. The central chromophore was an electro‐deficient fluorene‐malononitrile (FM) unit, that can be functionalized symmetrically on two different positions, giving rise to two positional isomers, called TAT‐ p FM and TAT‐ m FM, when the TATs are connected to the 2, 7‐ and 3, 6‐positions, respectively. The two isomers exhibited different electronic conjugation pathways that drastically affect their absorption properties and energy levels. Moreover, while TAT‐ p FM was organized in a stable 3D mesomorphic structure from room‐temperature to the melting point, TAT‐ m FM remained crystalline and decomposed before melting. Finally, despite a lower hole mobility, the TAT‐ m FM exhibited the highest Power Conversion Efficiency (PCE) of about 2 % in organic solar cells. This higher PCE was attributed essentially to the pronounced internal charge transfer band contribution to the charge photogeneration observed in TAT‐ m FM solar cells. Abstract : Two dumbbell‐shaped molecules isomers based on triazatruxene units sandwiching a fluorene‐malononitrile unit have been synthesized and studied. The isomers exhibited different solid‐state structures and electronic conjugation pathways, that drastically affect their absorption properties and energy levels. Photovoltaic performances have been investigated and correlated to the internal charge transfer band contribution to the charge photogeneration.